Tindak pidana pasar modal dan pengawasan perdagangan efek di bursa - Isharsaya Isharsaya (Universitas Islam Indonesia, 1997)
Actually, stock exchange markets us vulnerable to criminality, i.e: deception, market manipulation and insider trading, Hence, controlling is one of important obligation of Jakarta Stock Exchange (JSE) so that by the regulated, transparent and efficient trading is formed.